Wavefunction-based quantum-chemical ab initio calculations for core electron binding energies of small open shell molecules. (31st August 2022) - Staemmler, Volker
Abstract: Core electron binding energies (CEBEs), i.e. ionization energies of 1s core orbitals, are calculated by means of wavefunction-based quantum-chemical ab initio methods for a series of small open-shell molecules containing first-row atoms. The calculations are performed in three steps: (a) Koopmans' theorem, where the orbitals of the electronic ground state are used unchanged also for the ions, (b) Hartree–Fock or self consistent field (SCF) approximation in which the orbitals are allowed to relax after 1s ionization (ΔSCF), (c) dynamic correlation effects on top of SCF. For open-shell molecules 1s ionization leads to ions in several spin states, mostly to a pair of a triplet and a singlet state. In several cases one or both of these ionic states are only poorly described by a single-reference SCF wavefunction, therefore a multi-reference complete active space self consistent field (CAS-SCF) wavefunction is used instead. The correlation effects are evaluated by means of our multi-reference coupled electron pair approximation program. The accuracy of the calculated CEBEs is in the order of 0.1–0.4 eV. This is in agreement with experimental results for NO and O2 . But there exist only very few gas phase data for CEBEs of open-shell molecules.